Nineteenth-Century Homeopathic Materia Medica Texts Predict Source Materials Whose Physiological Actions Influence Thyroid Activity - Block, Janice (Homeopathy, 2019)
Introduction The homeopathic materia medica contains hundreds of thousands of observations collected over the course of two centuries. It includes both clinical observations of potentized medicines and observations of the actions of potentized medicines on healthy subjects (provings). This current study was undertaken to determine the degree to which observations within the materia medica were associated with the physiological mechanisms for thyroid activity-inhibiting substances in their undiluted state.Materials and Methods Four specific symptoms for iodine deficiency were selected to describe the hypothyroid state: (1) generalized aggravation by or sensitivity to cold; (2) chronic painless hoarseness; (3) goiter; (4) painless diffuse non-scarring alopecia. Symptom representation for the four selected symptoms within the homeopathic materia medica was compared for 2 halogen inhibitors, for 3 substances that influence thyroid hormone target tissues, for 6 substances known or suspected to increase thyroid-stimulating hormone or decrease thyroid hormone levels, and for 11 substances not known to inhibit thyroid activity. To avoid knowledge bias, only those compilations of materia medica whose publication dates preceded the discoveries of crucial aspects of thyroid physiology were used as source materials for investigation.Results Homeopathic medicines derived from 11 substances with mechanisms for inhibition of thyroid activity were more likely to exhibit selected symptoms than the medicines derived from the 11 substances without known physiological mechanisms for thyroid activity inhibition. The difference between groups was analyzed via the Mann–Whitney non-parametric U test and was statistically significant to p < 0.01. After observations obtained from provings alone were removed from analysis, the difference remained significant to p < 0.01. Only the two halogen inhibitors of iodine (bromine and fluoric acid) and one of the influencers of thyroid hormone target tissue (calcium carbonate) were significantly goitrogenic.Conclusions With respect to thyroid activity inhibition, there is a statistically significant association between observations recorded within the homeopathic materia medica and the expected physiological mechanisms for the corresponding undiluted substances.
Keywords: homeopathy; materia medica; hypothyroidism; physiological mechanism; nineteenth century